Collaborative activities for solving multi-step problems in general chemistry - Luis Antonio Tortajada-Genaro (OmniaScience, 2014)
The learning of solving multi-step problems is a relevant objective in chemical education for engineering students. In these questions, after analyzing initial data, a complex reasoning and an elaborated mathematical procedure is needed to achieve the correct numerical answer. But, many students are able to effectively use algorithms even with a lack of meaningful understanding of involved chemical concepts. This paper reports the application of some collaborative actions in order to induce a complete acquisition of problem solving skills. The studied approaches, performed inside and outside the classroom, are classified in low-collaborative and high-collaborative activities depending on the relative participation of instructor/students in their development. The critical description of proposed methodology and the produced outcomes are exposed. The contribution of each major reasoning mode (model, rule or case based) employed in these activities is analyzed. Also, the perception of students is evaluated based on the data provided by direct observation and a specific survey with Likert-scale and open-ended questions. The results indicate that the changes of teaching to a more conceptual orientation lead a deeper understanding, minimizing misconceptions or a rote learning.